Characteristics of the vaginal microbiota and vaginal metabolites in women with cervical dysplasia - Yu, Tiantian; Gao, Shan; Jin, Fen; Yan, Bingbing; Wang, Wendong; Wang, Zhongmin (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionEmerging evidence suggests that the vaginal microbiota is closely associated with cervical cancer. However, little is known about the relationships among the vaginal microbiota, vaginal metabolites, and cervical lesion progression in women undergoing cervical dysplasia.MethodsIn this study, to understand vaginal microbiota signatures and vaginal metabolite changes in women with cervical lesions of different grades and cancer, individuals with normal or cervical dysplasia were recruited and divided into healthy controls (HC) group, low-grade squamous intraepithelial lesions (LSIL) group, high-grade squamous intraepithelial lesions (HSIL) group, and cervical cancer (CC) group. Vaginal secretion samples were collected for 16S rRNA gene sequencing, liquid chromatography coupled with mass spectrometry (LC–MS)-based metabolomics, and integrated analysis.ResultsThe results demonstrated that bacterial richness and diversity were greater in the CC group than the other three groups. Additionally, Lactobacillus was found to be negatively associated with bacterial diversity and bacterial metabolic functions, which increased with the degree of cervical lesions and cancer. Metabolomic analysis revealed that distinct metabolites were enriched in these metabolite pathways, including tryptophan metabolism, retinol metabolism, glutathione metabolism, alanine, aspartate, and glutamate metabolism, as well as citrate cycle (TCA cycle). Correlation analysis revealed positive associations between CC group-decreased Lactobacillus abundance and CC group-decreased metabolites. Lactobacillus iners was both negative to nadB and kynU genes, the predicted abundance of which was significantly higher in the CC group. The linear regression model showed that the combination of the vaginal microbiota and vaginal metabolites has good diagnostic performance for cervical cancer.DiscussionOur results indicated a clear difference in the vaginal microbiota and vaginal metabolites of women with cervical dysplasia. Specifically altered bacteria and metabolites were closely associated with the degree of cervical lesions and cancer, indicating the potential of the vaginal microbiota and vaginal metabolites as modifiable factors and therapeutic targets for preventing cervical cancer.